Faith, Family, Fighter: The Story of Colonel Louis Hall DeLoss Crane - Hendricks, Wade (My University, 2017)
“For the Confederate bullet that ended the Beloit man’s career closed a life of romance and honorable achievement that will always be recorded in the history of this section of the country.” Many of the men who fought in the American Civil War did not know what it meant to be a soldier. The armies were very diverse. Enlistees varied greatly, by religious denominations, immigrant backgrounds, and family backgrounds to name a few. These lead to different reasons for men to enlist. Some enlisted to protect home, others because they were swayed by adventure, and others still for pay. Louis Hall DeLoss Crane fought for a different reason, because it was the right thing to do. Louis had a hatred for the institution of slavery. This was instilled in him at a young age, passed down through the vigorous bond of father and son. James, Louis’ brother, said of Louis, “inheriting his father’s patriotic zeal, Col. L.H.D. Crane yielded up his life in full vigor of early manhood on the battle field of Cedar Mountain, 1862. A hundred times he said to me, “This war will be an utter failure if it doesn’t result in the complete and utter destruction of slavery.”
Keywords: United States -- History -- Civil War, 1861-1865; Soldiers -- History -- 19th century -- United States; Soldiers -- Wisconsin -- Biography